ANALYSIS OF THE DEVELOPMENT OF CREATIVE ECONOMIC EDUCATION FOR THE COMMUNITY IN PREVENTING STUNTING IN PARTIHAMAN SAROHA VILLAGE - Fauziah Nur Simamora; Editha Dewi Purnamasari; Yenni Rosyinah Hasibuan (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2025)
This study aims to analyze the development of creative economy education as a community empowerment strategy to prevent stunting in Partihaman Saroha Village. Stunting is a health problem with long-term impacts on the quality of human resources. The creative economy approach is seen as having the potential to improve nutritional knowledge, family income, and access to nutritious food through innovative use of local resources. The research method used was a qualitative approach with data collection techniques including in-depth interviews, observation, and documentation studies. The results indicate that creative economy education, developed through skills training, processing of local agricultural products, and digital marketing, can increase community awareness of the importance of nutrition and strengthen family economic resilience. Thus, the development of creative economy education has been proven to make a significant contribution to supporting sustainable stunting prevention efforts at the village level.